Participatory cultures and knowledge generative scenarios: rereading 3D virtual worlds - Daniela Cuccurullo (Form@re : Open Journal per la Formazione in Rete, 2019)
In an Information society, the web 2.0, in its evolution towards 3.0, represents the most evident transformation of knowledge transmission from the Gutenbergian model into new forms of connective learning and shared knowledge through the global net. Networks permeate social life and daily relations, modify the forms of knowledge and give rise to new educational and training contexts, provoking osmotic flows of co-construction of knowledge. Through the presentation and analysis of some experimentation projects using 3D immersive virtual worlds in higher-education contexts, the contribution draws attention to the potential of these spaces as places of social and cultural aggregation, as socio-constructive learning environments of collective intelligence, as scenarios of participatory culture generative action.